The Most Common Predictors of Uncontrolled Blood Pressure Among Hypertensive Elders: A Systematic Review - Triyana Puspa Dewi; Aini Ahmad (International Journal of Advanced Health Science and Technology, 2023)
Aging process implies challenges for the elderly, specifically related to degeneration in the vascular system. The uncontrolled blood pressure has detrimental effects on brain, heart and kidney that cause organ failure. Hypertension is getting harder to control if the patients unaware with the factors that outweigh blood pressure control. Medication nonadherence and unhealthy behavior are known as the essential factors related to uncontrolled blood pressure. The study aims to assess the most common predictors of uncontrolled blood pressure, which involved elders with hypertension. The method used is a systematic review obtained from databases of Scopus, Science Direct, PMC, and SAGE. The total of eight full text articles in English language and randomized controlled trial design determined from 2018 to 2022 included in the assessed articles. The result did not reveal medication adherence as the most common factor, but obesity as modifiable predictor is obesity, whereas unmodifiable are age and comorbid. It is indicated that the require intervention for hypertensive elder is focused on body weight and comorbid management. The implication of this systematic review is beneficial for the elderly to achieve blood pressure control by enhancing the awareness of changeable factors and adopt a healthy lifestyle. Furthermore, the nurse also easier to determine the appropriate intervention for elders.